Pengaruh Kepemilikan Keluarga, Ukuran Dewan Direksi, Dan Proporsi Direktur Independen Terhadap Tingkat Pengungkapan Sukarela - Ridwan Ridwan; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine the effect of family ownership, board size, and the proportion of independent directors on the level of voluntary disclosure. This research is classified as causative research. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. By using the purposive sampling method, there are 57 companies as research samples. Family ownership is measured by the percentage of share ownership, the size of the board of directors is measured by the number of board of directors of the company, the proportion of independent directors is measured by the percentage of independent directors on board structure and voluntary disclosure is measured by the disclosure index. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is multiple linear regression. The results of this study show Family ownership has a negative and significant effect on the level of voluntary disclosure. The size of the board of directors has a positive and significant effect on the level of voluntary disclosure, and the proportion of independent directors has a positive and not significant effect on the level of voluntary disclosure.